Examining the Moderating Role of Patient Enablement on the Relationship Between Health Anxiety and Psychosomatic Distress: A Cross-Sectional Study at a Traditional Chinese Medicine Outpatient Clinic in Hong Kong - Chan, Celia H. Y.; Lau, Bobo H. P.; Chan, Timothy H. Y.; Leung, H. T.; So, Georgina Y. K.; Chan, Cecilia L. W. (Frontiers in Psychology, 2020)
Background: Little research effort has been devoted to examining the role of patient enablement in alleviating health anxiety in primary care. In this study, we examined the role of patient enablement as a moderator in the relationship between health anxiety and psychological distress and treatment seeking in traditional Chinese medicine. Methods: The participants were 634 patients of a government-subsided Chinese medicine outpatient clinic in Hong Kong. They were asked to complete a series of questionnaires on patient enablement, health anxiety, anxiety, depression, physical distress, annual clinic visits, and service satisfaction, and provided various demographic details. Descriptive statistics, correlations, and general linear models were used to analyze the data. Results: We found that patient enablement correlated positively with service satisfaction. Patient enablement also interacted significantly with health anxiety in affecting indices of psychological distress (depression, anxiety) and treatment seeking (annual visits). Among highly enabled patients, the positive association between health anxiety and indices of psychological distress was weakened, and they also showed more health anxiety-driven treatment seeking as measured by annual clinic visits. Conclusions: These findings suggest a moderating mechanism by which patient enablement weakens the relationship between health anxiety on psychological well-being and increases treatment-seeking behavior in traditional Chinese medicine. Practitioners are encouraged to provide sufficient information to patients to foster self-care and disease self-management using complementary and alternative medicine.